Differential expression of plasma exosomal microRNA in severe acute pancreatitis - Xu, Yansong; Sun, Yuansong; Yin, Ran; Dong, Tao; Song, Kai; Fang, Yang; Liu, Guodong; Shen, Bing; Li, He (Frontiers in Pharmacology, 2022)
The incidence rate of acute pancreatitis is increasing, and severe acute pancreatitis (SAP) is associated with a high mortality rate, which may be reduced by a deeper understanding of its pathogenesis. In addition, an early determination of the severity of acute pancreatitis remains challenging. The aim of this study was to match potential biomarkers for early identification and monitoring of acute pancreatitis and to shed light on the underlying pathogenic mechanisms of SAP. The expression levels of plasma exosomal microRNA (miRNA) in patients with pancreatitis have been associated with the disease. Thus, this study compared the expression levels of exosomal miRNA in plasma collected from four patients with SAP and from four healthy participants. Analyses of the miRNA expression profiles indicated that three previously unreported miRNAs were differentially expressed in the patient group: Novel1, which was downregulated, and Novel2 and Novel3, which were upregulated. The miRNA target genes for those novel miRNAs were predicted using Metascape. Of these miRNA target genes, those that were also differentially expressed at different time points after disease induction in a mouse model of acute pancreatitis were determined. The gene for complement component 3 (C3), a target gene of Novel3, was the only gene matched in both the patient group and the mouse model. C3 appeared at most of the time points assessed after induction of acute pancreatitis in mice. These findings are foundational evidence that C3 warrants further study as an early biomarker of SAP, for investigating underlying pathogenic mechanisms of SAP, and as a therapeutic target for ameliorating the occurrence or development of SAP.